Morality in the Marketplace : Reconciling Theology and Economics - Geest, Paul van, (BRILL, 2022)
What does Keynes have to do with Qohelet? At first sight, economy and theology seem to be disciplines with mutually exclusive objectives. Yet, as the Covid crisis has recently shown, if economic development is to really stand a chance of success, it should go hand in hand with relational values like honesty, reliability and empathy: this will contribute to a society with a culture of reciprocity, respect, love and trust. In this essay, Paul van Geest pleads for a renewal of the old ties between economics and theology as scientific disciplines, so as to arrive at a deeper and richer anthropological fundament for economic research.